Al-Baqillani’s thoughts on selected theological issues of the Qur’an / Much Hasan Darojat - Much Hasan, Darojat (2017)
This present research discusses al-BÉqillÉnÊ’s thoughts on theological issues related to the Qur’Én. It covers three significant problems; the createdness of the Qur’an, the anthropomorphists’ approach to the Qur’ān, and the authenticity of the Uthmanī muÎÍaf. Al-Bāqillānī categorised these issues into three different theological groups; Mu‘tazilites, antrophomorphists, and Shi‘ites. With the Mu‘tazilites, he rejected the problem of the createdness of the Qur’Én, which involves disscussion on the divine speech of God, meaning of speech, its chacacteristics and divisions, and other related topics. Al-BÉqillÉnÊ also disproved some theological doctrines formulated by the anthropomorphists in dealing with the Qur’ān and Íadīth. His criticisms included the extreme (Gulāt) Shi‘ites as well as the Øufis. Al-BÉqillÉnÊ also defended the authenticity of the Uthmānī muÎÍaf of the Qur’ān againts the Early Twelver Shi‘ites’ claim. He proved the validity of the muÎÍaf right from its compilation until it became the perfect codex employed by the authoritative companions. He also delineated their integrity who directly learnt from the Prophet (peace be upon him) on the seven variant readings of the Qur’ān. These readings are valid and approved by the Prophet (peace be upon him). In this study, the approach that was applied is textual analysis, using descriptive and analytical methods to investigate and analyze primary sources related to the issues. It also adopted the historical method to scrutinize several events on the subject. Al-BÉqillÉnÊ attempted to discuss these issues; the createdness of the Qur’Én, the anthropomorphic doctrines, and the authenticity of the Uthmānī muÎÍaf of the Qur’Én by developing its principles in accordance with the theological position of al-Ash‘arīte’ views. He was one of those who initiated the intellectual initiative to deepen the level of intellectual discourse on some of the principal foundations in the theological thoughts of this school. In his intellectual undertaking in tackling those issues, he also provided a number of relevant arguments againts the Orientalists’ critiques regarding the above related subject.